May-Thurner syndrome: a review - Valderrama-Treviño, Alan I.; Lacayo-Valenzuela, Marlon; Olivares-Cruz, Sandra; Escareño, Hugo Laparra; Pittaluga, Ernesto Pacheco; Barrera, Germ´án E. Mendoza; Iglesias-González, Pablo C.; Colón, José A. Barajas; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2024)
May-Thurner syndrome (MTS) is an underdiagnosed entity and level of suspicious should be raised during evaluation of deep vein thrombosis (DVT) of the left lower limb, especially in women between the third and fifth decades of life. To correctly identify MTS, high clinical suspicion, and imaging studies such as phlebography, magnetic resonance imaging (MRI), computed tomography (CT), and intravascular ultrasound are required. In correct clinical context, CT/MRI venography can be used to facilitate early diagnosis and treatment that includes pharmaco-mechanical thrombolysis with angioplasty and stenting, both of which minimize late morbidity from post-thrombotic syndrome.